IDENTIFIKASI PENYAKIT TEGAKAN KEMIRI (Aleurites moluccanna WILD) PADA UMUR 7 DAN 10 TAHUN DI DESA TOAYA KECAMATAN SINDUE KABUPATEN DONGGALA - Victor, Victor; Rahmawati, Rahmawati; Yusran, Yusran (Universitas Tadulako, 2016)
Hazelnut plant consisted of several types, including Aleurites moluccanna derived from Malaya Peninsula, Aleuritis fordi derived from China middle and montana grows in subtropical areas and allegedly originated from South China and Indochina Aleurites cordata from Japan to grow on the island near Tokyo. The nature of hazelnut plant species differ from one another Aleurites moluccanna wild plant height can reach 39 m with a trunk diameter of 110 cm. This plant was grown as a crop ever reforestation to cover the sandy hills in Java. The purpose of this study was to determine the types of disease, symptoms of frequency and intensity of the residual disease hazelnut (Aleurites moluccanna Willd) in the village Toaya Sindue District of Donggala Regency. This research was started in May - July 2014 stands hazelnut area in the village Toaya Sindue Donggala District of Central Sulawesi province. Identification of symptoms (symptoms) done by looking at the physical plant changes due to disease, such as the existence of cancer stem on pecan stands. To determine the types of diseases that attack plants used identification method is direct observations in the field. For species not yet known, the sample was taken and subsequently collected in the identification of the agriculture faculty in a Tadulako University laboratory for identification purposes. The results showed that the types of pathogens that attack the disease stands hazelnut (Aleurites moluccanna Willd) at the age of 7 and 10 in the village of Toaya there are 4 types including leaf blight disease, cancer stem, leaf spot diseases and diseases of the stands hazelnut (Aleurites moluccanna Willd ). By the age of 7 years on average was 63.3% and 39.8%, and at age 10 the average was 66.5% and 36.3%. Criteria residual damage hazelnut (Aleurites moluccanna Willd) by the age of 7 and 10 years, including being damaged criteria.Keywords: Identification, Disease, Stands, Pecans.